Implementation of the National Insight Values of Hamengku Buwana IX For Character Education - Wignjosasono, Ken Widyatwati (Universitas Syiah Kuala, 2023)
The noble values and national insight of Hamengku Buwana IX, who was nationalist and democratic, played an important role in shaping the character of the younger generation. So that as the next generation of the nation they not only have intellectual intelligence but also have emotional intelligence. This qualitative research with historical approach uses descriptive analysis method to find the noble values and national insight of Hamengku Buwana IX. The results showed that the leadership values and national insight of Hamengku Buwana IX in respecting ancestral culture and prioritizing the interests of the nation and state were the basis for character education and noble character education. Hamengku Buwana IX is able to combine traditional and modern thinking, which refers to noble values and national insight by prioritizing the interests of society and the state in his leadership. So that character education for the younger generation can be directed at emphasizing the noble values and national insight of Hamengku Buwana IX.